PENGARUH MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. BERDIKARI LOGISTIK INDONESIA CABANG PEKANBAR - Nurhayana, Nurhayana (Eko dan Bisnis: Riau Economic and Business Review, 2018)
This research did in PT. Berdikari Logistic Pekanbaru Indonesia. The title of this research about the influence of motivation on employee productivity at PT. Berdikari Logistic Pekanbaru Indonesia, with the sample in this research are 53 people. The result of this research were motivation have positive and significant influence on employee productivity at PT. Berdikari Logistic Pekanbaru Indonesia. The instrument used in this research was simple linier regression, t-test, and determination. In the test of  validity, all of items was valid because have value  rhitung > rtabel (0.270), The result of simple linier regression was Y= 1.464 + 1.057X. From the result of t-obtained was thitung (10.347) > ttabel (200758). Which was the level sig 0.000 <0.05 it means that the variable of motivation have positive and significant influence on employee productivity. And determination coefficient value R2 was 0.677 or 67.7%, it means the influence or contribute which was provided by variable of motivation  to variable of  productivity was 67.7% while the rest was 32.3% influenced by another factors which was not concern in this research